Interaction between C18 fatty acids and DOPE PEG2000 in Langmuir monolayers: effect of degree of unsaturation - Gew, Lai Ti *; Misni Misran, (Springer, 2017)
In this study, we address the effect of the cis-double bond in 1,2dioleoyl-sn-glycero-3-phosphoethanolamide-N-[methoxy(polyethylene glycol)-2000, DOPE PEG2000 (DP), on the Langmuir monolayer of C18 fatty acids—namely, stearic acid (SA), oleic acid (L1), linoleic acid (L2), and linolenic acid (L3)—with the same head group but different degrees of saturation on their hydrocarbon chains. Negative values of Gibbs free energy of mixing (ΔGmix) were obtained throughout the investigated ranges of the unsaturated C18 fatty-acid (L1, L2 and L3) mixed systems, indicating that very strong attractions occurred between molecules in the monolayers. The bend and kink effects from the cis-double bond(s) in the hydrocarbon chain affected the membrane fluidity and molecular packing in the monolayers, which resulted in a greater interaction between unsaturated C18 fatty acids and DP. The most thermodynamically stable mole composition of unsaturated C18 fatty acids to DP was observed at 50:1; this ratio is suggested to be the best mole ratio and will be subsequently used to prepare DP–C18 fatty-acid nanoliposomes. The presence of cis-double bonds in both hydrocarbon chains of DOPE in DP also created an imperfection in the membrane structure of lipid-drug delivery systems, which is expected to enhance lipid-based systems for antibody conjugation and drug encapsulation